Exploring the environmental Kuznets hypothesis: Theoretical and econometric problems - Georg Müller-Fürstenberger; Martin Wagner (Institute for Advanced Studies (IHS), 2006)
Focussing on the prime example of CO2 emissions, we discuss several important theoretical and econometric problems that arise when studying environmental Kuznets curves (EKCs). The dominant theoretical approach is given by integrated assessment modelling, which consists of economic models that are combined with environmental impactmodels. We critically evaluate the aggregation, model dynamics and calibration aspects and their implications for the validity of the results. We then turn to a discussion of several important econometric problems that go almost unnoticed in the literature. The most fundamental problems relate to nonlinear transformations of nonstationary regressors and, in a nonstationary panel context, to neglected cross-sectional dependence. We discuss the implications of these two major and some minor problems that arise in the econometric analysis of Kuznets curves. Our discussion shows that EKC modelling as performed to date is subject to major drawbacks at both the theoretical and the econometric level.
Keywords: Q20; C12; C13; 330; carbon Kuznets curve; integrated assessment models; regressions with integrated variables; nonstationary panels; Kohlendioxid; Schätztheorie; Environmental Kuznets Curve